Concentration of mass in the pressureless limit of the Euler equations of one-dimensional compressible fluid flow. (April 2020) - Sheng, Shouqiong; Shao, Zhiqiang
Abstract: In this paper, we study the limiting behavior of Riemann solutions to the Euler equations of one-dimensional compressible fluid flow as γ tends to one. We show that the limit solution forms the delta wave to the pressureless Euler system of one-dimensional compressible fluid flow in the distribution sense. Some numerical results exhibiting the phenomena of concentration are also presented.